Investigating the operational issues of Islamic hotel business in Malaysia: a conceptual paper / Nur Iman Hashim and Nadzirah Mohd Fauzi - Hashim, Nur Iman; Mohd Fauzi, Nadzirah (Center for Islamic Philantrophy & Social Finance (CIPSF), 2020)
The increasing demand over Shariah compliant services since past one decade has significantly contributes to the development of Islamic hotel business in Malaysia. Several factors such as the increasing number of global Muslim population, high disposable income among Muslims and high awareness on getting Shariah compliant services becoming the main contributors to the growing of this business segmentation. However, it is reported by many scholars that this business segment is still not stable since there are loopholes mentioned by previous scholars found in the operational side of Islamic hotel business. Concerned to determine the extent to which this business segment is still not stable, several journal articles was selected and reviewed by this research. It is hope that this paper will be able to provide a comprehensive information related to the inadequacy in the Islamic hotel business in Malaysia and at the same time serving as an idea for future research in this area of interest.